ANALISIS USAHA PRODUK DIMSUM TUNA GLEDEK - Novie Wijaya; Meilya Suzan Triyastuti; Nanung Syaiful Rijal; Feronica Umboh (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2025)
The City of Bitung has produced a significant increase in tuna production. Tuna is a superior raw material at the Bitung. Handling the correct quality of fresh fish and the need for diversification of fishery products such as dimsum tuna. This study aims to determine the feasibility of the tuna gledek dimsum business. This research uses a descriptive method and feasibility analysis. The results of the feasibility analysis of the RCR value is 1.5, the PP value is 1.9 months and the ROI is 1%. This shows that the tuna gledek dimsum business is feasible to run.